Penerapan MCDA untuk Meningkatkan Kesadaran Keamanan Informasi Publik pada Dinas Dukcapil Kota Bengkulu - Ferzha Putra Utama; Desviansyah Yoga Prasetyo; Funny Farady Coastera (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
The Population and Civil Registration Office (Dukcapil) of Bengkulu City is the implementing element of the Regional Government, which organizes the formulation and implementation of policies in the population and civil registration field. In its implementation, Bengkulu City Dukcapil employees serve as information data processors for the people of Bengkulu City. Dukcapil has applied information technology to support processing information data, including the Electronic Citizen Administration Service System (Slawe) and the Population Administration System (Siak). The level of employee awareness on information security is one of the critical factors in using technology. Weak awareness can lead to problems in information security, such as misuse and leakage of information. This study aims to measure the level of information security awareness for employees of Dukcapil Kota Bengkulu. The method used is Multiple Criteria Decision Analysis (MCDA), which can measure alternative values based on established criteria. Observation, interviews, questionnaires, and literary studies were used to collect data. This study uses three dimensions of consciousness in the object of research to determine the level of consciousness, namely Attitude, Behavior, and Knowledge. Furthermore, the measurement results are then categorized into three variables (poor, medium, and good) using the AHP method. In the end, recommendations will be given on poor and moderate value aspects. The results of this study show that the level of information security awareness of Bengkulu City Dukcapil Employees is at a